Pengembangan Multimedia Interaktif Berbasis Unity Pada Subtema Keberagaman Budaya Bangsaku di Kelas IV Sekolah Dasar - Muhammad Sofwan; Moch Bayu Eko Wibowo (Jurnal Gentala Pendidikan Dasar, 2019)
This research is a research development that aims to be able to produce interactive multimedia products based on a valid and practical unity. The results of the development were then tested on SD N 47 / IV Jambi City in class IV.F with a total of 30 students. This research was conducted at SD N 47 / IV Jambi City. The research data were obtained by validating media experts, validating learning experts, teacher questionnaires and student questionnaires, which were strengthened by documentation data. After the data is obtained, then a percentage of the data is searched using a predetermined formula to see the feasibility of the developed media. The types of data used in this study are qualitative and quantitative data. Based on the results of this study, teachers are expected to be able to develop a technology-based media with the aim of creating enjoyable learning and creating a new atmosphere in the classroom that can be concluded that the development of Unity-Based Interactive Multimedia in the Sub-theme of Cultural Diversity of Banngsaku in Class IV Elementary Schools is included in the category valid and practical.